[PP.26.20] THE NEW COMBINATION TRIAL BY TRADITIONAL CHINESE MEDICINE OF TIANMA-GOUTENG DECOCTION AND L-AMLODIPINE BESYLATE IN PATIENTS WITH ESSENTIAL HYPERTENSION. (September 2016) - Liu, Y.; Du, L.F.; Liu, X.; Fan, Y.
Abstract : Objective: It is rare trial that combining traditional Chinese and western medicine to treat hypertension. The aim of this study is to investigate the effect, advantages and safety of combining TCM of tianma-gouteng decoction and L-amlodipine besylate in essential hypertensives (EH). Design and method: 150 patients with EH were randomly divided into two groups: control group (n = 75) were treated with L-amlodipine besylate 2.5 mg qd; treatment group (n = 75) were treated with the same dose of L-amlodipine besylate plused TCM 150 ml tid. The data were assessed at baseline and after treatment for 4 weeks. Results: After treatment, the symptoms in the two groups were relieved and were earlier and more significant in treatment group (P < 0.05). 24hSBP, 24hDBP, dSBP, dDBP, nSBP, nSBP, dSBPL, dDBPL, nSBPL and nDBPL were declined obviously compared to baseline(all P < 0.01) in every group. 24hSBP, dSBP, nSBP and dSBPL, nSBPL were declined significantly in treatment group than in control group after treatment[(137.09 ± 12.71) vs (131.28 ± 11.90), (139.07 ± 13.12) vs (132.35 ± 10.77, (131.50 ± 12.61) vs (122.93 ± 13.16) mmHg and (46.67 ± 32.18)% vs (29.47 ± 23.93)%, (62.21 ± 31.35)% vs (43.19 ± 32.11)%, all P < 0.05]. However, 24hDBP, dDBP, nDBP and dDBPL, nDBPL were no significant difference between two groups [(83.26 ± 10.07) vs (82.91 ± 9.34, (85.50 ± 13.72) vs (84.68 ± 10.28) g, (79.61 ± 12.57) vs (78.13 ± 11.18) mmHg and (38.38 ± 30.67)% vs (37.70 ± 28.63)%, (46.80 ± 31.75)% vs (46.19 ± 30.35)%, all P > 0.05)]. No serious side effects were observed in two groups. Conclusions: (1)The symptoms of EH can be relieved obviously by TCM or L-amlodipine besylate. (2) TCM can reduce 24hSBP, dSBP and nSBP and can not reduce 24hDBP, dDBP and nDBP. (3) There are mult-aspect advantages of combining TCM with L-amlodipine besylate. This is a new way With clinical significance to treat hypertension by combination therapy.